Budget Efficiency In The 2025 Regional Budget (Apbd) Planning Of West Java Province (A Policy Response To Presidential Instruction No. 1 Of 2025) - Astika, Dewa; Tri P., Chrisyanto; Alim, Muhammad Syahrul (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
Public budget efficiency is a strategic issue that is critically important in government governance, especially in the context of fiscal decentralization currently underway in Indonesia. In an effort to enhance the quality of public financial management, Presidential Instruction Number 1 of 2025 has been established as a significant policy milestone. This instruction emphasizes the need for more efficient, productive, and performance-based budget planning. This is particularly relevant given the challenges faced by regional governments in managing limited financial resources while remaining committed to achieving broader development goals.In this context, the Provincial Government of West Java, which is one of the regions with the largest Regional Revenue and Expenditure Budget (APBD) allocations in Indonesia, is faced with increasing demands to reform its budget planning. This reform includes reducing unproductive spending, avoiding program overlaps, and ensuring strong synergy between regional development programs and the national objectives that have been set. Thus, budget efficiency is not only a necessity but also a strategic step towards improving community welfare. However, in practice, the application of efficiency principles often clashes with sectoral bureaucratic patterns, where each regional apparatus organization (OPD) tends to operate in separate silos. This results in program overlaps and suboptimal resource utilization. Additionally, the weakness of the performance evaluation system also becomes a significant hindrance to achieving budget efficiency. These challenges reinforce the urgency to examine the extent to which the 2025 APBD of West Java has concretely and systematically responded to the presidential directives. This research aims to fill the existing research gap by focusing on the analysis of the APBD structure, cross-sectoral planning dynamics, and the effectiveness of budget allocation based on development priorities. Through a comprehensive analytical approach, this study aims to provide deeper insights into how budget efficiency policies can be effectively implemented at the regional level, as well as to identify the strategic steps needed to enhance budget management performance in West Java Province. Thus, the results of this research are expected to contribute meaningfully to the development of more responsive and accountable public policies, as well as to support the achievement of sustainable development goals